The right to work: transition from free dismissal to guaranteed constitutional right - Villavicencio Ríos, Alfredo (2013)
After presenting the evolution of labor stability law in Peru, public and private scopes of the right to work are described allowing the Constitutional Court redefine dismissal regime (working stability of exit), in general, and specifying temporary recruitment regime (working stability of entry). Redefinition of dismissal legal framework is analyzed from constitutional and judicial case law stressing solved and pending issues.